Complete Dependence on CD4+ Cells in Late Asthmatic Response, but Limited Contribution of the Cells to Airway Remodeling in Sensitized Mice - Takeshi Nabe; Toyoko Morishita; Kouki Matsuya; Ayumu Ikedo; Masanori Fujii; Nobuaki Mizutani; Shin Yoshino (Elsevier, 2011)
Abstract.: It is known that the late asthmatic response (LAR), a characteristic feature of asthma, is closely associated with CD4+ Th2 cell-mediated allergic inflammation. Airway remodeling is also a pathogenesis of asthma, but literature reporting roles of CD4+ cells in the remodeling is controversial. There has been no study that simultaneously assessed the roles of CD4+ cells in both LAR and airway remodeling. Sensitized mice were intratracheally challenged with ovalbumin 4 times. Treatment with an anti-CD4 monoclonal antibody (mAb) before the 1st challenge almost completely abolished increase in CD4+ cells in the tissues after the 4th challenge. The late phase increase in airway resistance after the 4th challenge was also completely inhibited by anti-CD4 mAb. Parameters of airway remodeling, subepithelial fibrosis and epithelial thickening were attenuated by treatment, whereas the inhibition was only 30% - 40%. Bronchial smooth muscle thickening was not affected. Because interleukin (IL)-5 production as well as eosinophilia was effectively suppressed by anti-CD4 mAb, the effect of anti-IL-5 mAb was also examined, resulting in no inhibition of airway remodeling. Collectively, although the LAR was completely dependent on CD4+ cell activation, airway remodeling was only partially dependent on the cell. Keywords:: airway remodeling, late asthmatic response, CD4+ cell, interleukin-5, fibrosis